Fitness Advantage of mcr-1–Bearing IncI2 and IncX4 Plasmids in Vitro - Wu, Renjie; Yi, Ling-xian; Yu, Lin-feng; Wang, Jing; Liu, Yiyun; Chen, Xiaojie; Lv, Luchao; Yang, Jun; Liu, Jian-Hua (Frontiers in Microbiology, 2018)
The objective of this study was to assess the impact of diverse plasmids bearing colistin resistance gene mcr-1 on host fitness. Forty-seven commensal E. coli isolates recovered from the pig farm where mcr-1 was first identified were screened for mcr-1. mcr-1-bearing plasmids were characterized by sequencing. The fitness impact of mcr-1-bearing plasmids was evaluated by in vitro competition assays. Twenty-seven (57.5%) E. coli isolates were positive for mcr-1. The mcr-1 genes were mainly located in plasmids belonging to IncI2 (n=5), IncX4 (n=11), IncHI2/ST3 (n=8), IncFII (n=2), and IncY (n=2). InHI2 plasmids also carried other resistance genes (floR, blaCTX-M, and fosA3) and were only detected in isolates from nursery pigs. Sequences of the representative mcr-1–bearing plasmids were almost identical to those of the corresponding plasmid types reported previously. An increase in the fitness of IncI2- and IncX4-carrying strains was observed, while the presence of IncHI2, IncFII and IncY plasmids showed a fitness cost although an insignificant fitness increase was initially observed in IncFII or IncY plasmids-containing strains. Acquisition of IncI2-type plasmid was more beneficial for host E. coli DH5α than either IncHI2 or IncX4 plasmid, while transformants with IncHI2-type plasmid presented a competitive disadvantage against IncI2 or IncX4 plasmid containing strains. In conclusion, IncI2, IncX4, and IncHI2 were the major plasmid types driving the dissemination of mcr-1 in this farm. Increased fitness or co-selection by other antimicrobials might contribute to the further dissemination of the three epidemic mcr-1–positive plasmids (IncI2, IncX4 and IncHI2) in this farm and worldwide.